Exploring the spiritual in the pedagogy of Friedrich Froebel - Best, Ron (International journal of children's spirituality, 2016)
Friedrich Froebel (1782-1852) was the inventor of the kindergarten, and his emphasis on childcentredness and play influenced the progressive movement throughout the world. The concepts of unity and wholeness are highly visible in his writings. Religion is addressed in his work and that of his followers, but little attention has been paid to spirituality per se in Froebel's thought. This paper explores the place of the spiritual in Froebel's scheme and in some of what has been written about him. It notes his use of the concepts of the spirit and spirituality, and considers the relationship between his faith and the Christian religion. It discusses the laws' which Froebel enunciated: of Divine Unity, opposites and the connection of opposites; the principle of self-activity; and the process of unfoldment'. These principles are observed in his teaching methods and resources, specifically in the Gifts and The Mother-Song Book of 1844. The paper concludes with a discussion of the implications for such concepts as the spirit of the child and spiritual education. The picture that emerges is of a child-centred education which honours the integrity of childhood. It is argued that such an education, fully embraced, is a spiritual education.